Tribute to Lois Ehrenburg at Jon Jon's - Watkins, Howard::::::::: (1981)
Bruce Bronzan speaking at portable microphone; Margaret Sharp, Karen Humphrey, Dale Doig, Lois Ehrenburg, Mary Nelson, Jim O'Banion, ?